2017
DOI: 10.1093/schbul/sbx021.212
|View full text |Cite
|
Sign up to set email alerts
|

154. Impaired Glucose Homeostasis in First-Episode Schizophrenia: A Meta-Analysis

Abstract: Between group comparisons revealed that those with social anxiety did indeed have worse social functioning, particularly in the domains of interpersonal communication (t(45) = 2.28, P = .025) and engagement (in conversations; t(45) = 2.89, P = .000). Participants with high social anxiety also had more difficulties in recognizing neutral emotional faces, compared to individuals with schizophrenia without social anxiety (t(31) = 2.19, P = .036).Although not specific to social anxiety, results on the facial emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 0 publications
7
90
1
2
Order By: Relevance
“…In this study, we found that antipsychotic-naïve FEP patients did not significantly differ from CS in their baseline measurements of fasting plasma levels of insulin, C-peptide and adiponectin. These findings are in contrast to previous studies reporting higher levels of insulin and C-peptide levels in the FEP patients' group compared to those in CS (Pillinger et al, 2017;Wu et al, 2013). However, other studies found no significant difference in insulin resistance between drug-naïve patients with psychosis and CS (Arranz et al, 2004;Sengupta et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we found that antipsychotic-naïve FEP patients did not significantly differ from CS in their baseline measurements of fasting plasma levels of insulin, C-peptide and adiponectin. These findings are in contrast to previous studies reporting higher levels of insulin and C-peptide levels in the FEP patients' group compared to those in CS (Pillinger et al, 2017;Wu et al, 2013). However, other studies found no significant difference in insulin resistance between drug-naïve patients with psychosis and CS (Arranz et al, 2004;Sengupta et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…In patients with FEP, our cumulative analyses on glucose metabolism outcomes are in line with previous meta‐analyses, which showed significant increases in fasting insulin levels and impaired oral glucose tolerance in this patient population (Greenhalgh et al, ; Perry et al, ; Pillinger et al, ). Our meta‐analysis also confirms previous reports of an impaired oral glucose tolerance in first episode, treatment‐naïve patients with mood disorders (Garcia‐Rizo et al, ; Guha et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…While research regarding glucose metabolism in treatment‐naïve, first episode patients with individual SMI suggest a pre‐diabetic condition, we have limited knowledge on the differences of glucose metabolism across different diagnostic categories of SMIs. Therefore, the first aim of this study is to extend previous findings in patients with FEP (Greenhalgh et al, ; Perry et al, ; Pillinger et al, ) by conducting a systematic review and a meta‐analysis of glucose intolerance in first episode, treatment‐naïve patients with FEP, as well as first episode, treatment‐naïve patients with depression and bipolar disorder. The second aim of this study is to compare the differences of pooled results from glucose metabolism outcomes between these diagnostic categories.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is an important finding as those with schizophrenia often display perturbations in glucose homeostasis prior to treatment with SGAs (Bergman and Ader, 2005;van Nimwegen et al, 2008;Pillinger et al, 2017). Repeated, transient excursions in blood glucose are harmful as they may lead to cardiovascular complications including impaired endothelial function and increased oxidative stress (Ceriello et al, 2008).…”
Section: Downloaded Frommentioning
confidence: 99%